Volunteer activity centres in the structure of educational work with students in Belarus: socio-legal aspect - Pokhomova, Alesya A.; Berazuik, Liliya A. (Journal of the Belarusian State University. Philosophy and Psychology, 2024)
The article analyses the experience of organising volunteer activity of students through the implementation of education work in higher education institutions of Belarus. As a rule, the methodological function when working with volunteer students is usually performed by the volunteer activity centres of higher education institutions, as well as the Republican Volunteer Centre. The results of the interdisciplinary study of student volunteering conducted in December 2023 are described. Recommendations on further development of the volunteer movement among students of higher education institutions of Belarus are presented.
Keywords: student volunteering; volunteer activity centre; educational opportunities; areas of educational work; interdisciplinarity; recipients of gratuitous assistance; legal regulation of volunteer activity